Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
Large yellow croaker Larimichthys crocea is a major mariculture species in China, achieving an annual yield of 292,615 tons by 2024. Commercial production faces considerable challenges from disease outbreaks, necessitating comprehensive immune mechanism research. Through comprehensive genomic and transcriptomic investigations, scientists have identified distinguishing characteristics within the L. crocea immune system, encompassing robust innate defense mechanisms, marked by the expansion of pattern recognition receptor lineages, antimicrobial peptide gene families, and antiviral defense‐related genes, and well‐developed adaptive immune capabilities. The current review outlines the molecular foundations underlying immune responses in L. crocea , highlighting the cooperative interplay between innate and adaptive defense systems when confronting pathogenic threats and environmental fluctuations. It bridges basic scientific inquiry with practical aquaculture implementation, exploring disease control strategies. Available evidence indicates possibilities for strengthening disease resistance through precision immunomodulation and improved aquaculture methods. Priority research areas encompass elucidating host‐pathogen relationships and establishing practical disease prevention protocols for industrial‐scale operations.